Windfall Management for Poverty Reduction : Improving Public Finance Management, The Case of Chad - Toto Same, Achille (World Bank, Washington, DC, 2012)
This paper aims at providing a guide to ensure efficiency in the management of Chad's windfall to support the development process and poverty reduction. The analysis is based on the lessons and experience of countries that have successfully used natural-resource-generated windfalls to launch their development process while avoiding the natural resource curse. The paper also discusses the petroleum management arrangements in place in Chad for poverty reduction. The author argues that the successful management of Chad's windfall for poverty reduction will depend on the effectiveness of oil revenue management arrangements in place in Chad and the government's willingness to improve public finance management (PFM).